PENINGKATAN SIKAP KOLABORATIF PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV MELALUI MODEL PEMBELAJARAN KOOPERATIF METODE TWO STAY TWO STRAY (TSTS) - Deby Fitriana; Suranto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to improve students' collaboration skills through the Two Stay Two Stray (TSTS) type cooperative learning model in Science and Nature subjects (IPAS). From the results of initial observations carried out in class IV in science and science learning, there were findings that students had not demonstrated collaboration skills with other students. This research uses classroom action research methods. The subjects in this research were 27 students in class IV A of SD Muhammadiyah 2 Kauman Surakarta. The research instruments used were student evaluation sheets and worksheets. The data analysis technique uses qualitative techniques. To determine the improvement of students, it is carried out in stages in 2 cycles. Based on the research results, it can be concluded that class IV science learning by implementing the Two Stay Two Stray (TSTS) type cooperative model is considered to be able to increase students' cooperative activities. The results of the research showed that there was an increase made in cycles I and cycle II in percentages. This was proven by the students' behavior in the second cycle showing more cooperation between group members.